2021
DOI: 10.1002/ppul.25351
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in cystic fibrosis survival in Mexico: Impact of socioeconomic status

Abstract: Background: Median survival age in cystic fibrosis (CF) has increased in developed countries. Scarce literature exists about survival in Latin America, especially in Mexico. The aim of our study was to assess the median age of survival in CF patients and the impact of risk factors in Mexico over a 20-year period. Methods: We conducted a retrospective study with all patients registered and followed in the CF Center in Monterrey, Mexico from 2000 to 2020. Median survival age was the primary outcome, assessed wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 29 publications
1
5
0
1
Order By: Relevance
“…In a previous study carried out by our group, the median age of survival for CF patients followed in a specialized center was 21 years; however, when patients were compared by socioeconomic status, the median age of survival in patients with high socioeconomic level reached 29 years compared to 15 years in the low socioeconomic level. 4 Accordingly, in the current study we observed a lower median age at death in the uninsured population when compared to the cases with medical insurance, which can be a reliable substitute of socioeconomic level.…”
Section: Despite Prominent Advances In Diagnosis and Treatment Cfsupporting
confidence: 51%
See 1 more Smart Citation
“…In a previous study carried out by our group, the median age of survival for CF patients followed in a specialized center was 21 years; however, when patients were compared by socioeconomic status, the median age of survival in patients with high socioeconomic level reached 29 years compared to 15 years in the low socioeconomic level. 4 Accordingly, in the current study we observed a lower median age at death in the uninsured population when compared to the cases with medical insurance, which can be a reliable substitute of socioeconomic level.…”
Section: Despite Prominent Advances In Diagnosis and Treatment Cfsupporting
confidence: 51%
“…3 Previous research by our study group reported a median age at death of 15.5 years during the 2016−2020 period in Mexico. 4 However, in Mexico a national patient registry is currently lacking, therefore the information available is from individual centers and does not cover the entire country's CF population. To contribute to the characterization of CF epidemiology in Mexico, the aim of this study was to analyze the CF-related mortality trends in the Mexican population during a 22-year period (1999−2020) using death certificates data.…”
mentioning
confidence: 99%
“…Worldwide, the disparity in CF‐survival between ethnicity is linked to socioeconomic status (SES) and quality of healthcare 12,26 . In a recent study from Mexico, low SES was associated with a fourfold increased risk of mortality with a significantly lower median survival age of 15.1 years in the low SES group compared to 29.4 years in the high SES group 27 . Although SES was not recorded in the SA cohort, ethnicity is a proxy for SES in SA where although being in the minority, average household income in Caucasians is significantly higher than non‐Caucasians 28 .…”
Section: Discussionmentioning
confidence: 99%
“…12,26 In a recent study from Mexico, low SES was associated with a fourfold increased risk of mortality with a significantly lower median survival age of 15.1 years in the low SES group compared to 29.4 years in the high SES group. 27 Although SES was not recorded in the SA cohort, ethnicity is a proxy for SES in SA where although being in the minority, average household income in Caucasians is significantly higher than non-Caucasians. 28 The higher mortality in non-Caucasian children under 10 years of age observed in this study is a surrogate for SES disparities between ancestries that still exist in SA today as a legacy of Apartheid.…”
Section: Analysis Of Age-specific Mortality By Time Periodmentioning
confidence: 99%
“…The healthcare disparities presented by Kaur et al are not unique to India, but also seen in other low‐ and middle‐income countries (LMIC) 7 . Filho et al report similar challenges faced in Brazil, South Africa, and Israel, while Bustamante et al reported disparities in CF‐survival in Mexico 8 …”
mentioning
confidence: 94%